Sex differences in migration routes and non-breeding areas of a declining shorebird - Ann E McKellar; Cheri L. Gratto-Trevor; T. Lee Tibbitts (Avian Conservation and Ecology)
Migratory birds face different threats and pressures across their annual cycle, and understanding the impact of these factors on individuals is critical to the conservation of avian populations. Individuals from the same breeding population may share the same non-breeding areas, and thus experience similar conditions, or they may travel to different habitats or regions during migration and the stationary non-breeding period. Marbled Godwits ( Limosa fedoa ) breeding in the Northern Great Plains, which have experienced steep population declines, are thought to spend the non-breeding period primarily on the Pacific Coast of the United States and Mexico. However, little is known about migratory routes, stopover sites, and non-breeding locations of specific breeding populations, nor whether individuals from the same breeding population remain together throughout the year. We deployed satellite transmitters on four mated pairs of godwits breeding in southern Alberta, Canada, with individuals tracked over a mean of 2.2 annual cycles (range 0.6–5.6, excluding one unit that stopped transmitting immediately following deployment). Counter to our expectations, females and males separated completely following breeding, with females traveling to non-breeding areas along the coast of California, United States, and males stopping over at Great Salt Lake, Utah, United States, and spending the non-breeding period in Baja California Sur, Mexico, a distance of ~1300 km from their mates. Despite spending nine months apart, individuals from this breeding population have previously been shown to have high mate fidelity. Interestingly, individuals mostly used protected areas during the non-breeding period, in contrast to the human-modified agricultural landscapes that make up the majority of their breeding grounds. Despite a small sample size, our results suggest a strong pattern of differential migration based on sex, with implications for the specific environmental conditions, and potentially threats, faced by female and male godwits across the annual cycle.